Undergraduate students satisfaction in the context of teaching and non teaching, Universiti Teknologi MARA / Noorfadzilah Mohd Fadzi... [et al.] - Mohd Fadzil, Noorfadzilah; Kassim, Shamshul Anaz; Mhd Nasir, Nurul Farihin; Ali, Jati Kasuma (Universiti Teknologi MARA, Kedah, 2017)
This paper outlines an empirical study, which seeks to identify the determinants of academic experience, faculty and teaching quality, campus life, facilities, placement and internship support, and competencies towards undergraduate students satisfaction at Universiti Teknologi MARA (UiTM). The purpose of this study is to investigate undergraduate students satisfaction in the context of higher education. This study investigates the relationship between academic experience, faculty and teaching quality, campus life, facilities, placement and internship support, and competencies. The total of 340 respondents were involved in this study. The survey result from the undergraduate students showed four independent variables which have a positive impact on the undergraduate students satisfaction: facilities, placement and internship support, competencies and academic experiences. In addition, faculty and teaching quality and campus life did not contribute much to undergraduate students satisfaction.